2014
DOI: 10.1093/mmy/myt022
|View full text |Cite
|
Sign up to set email alerts
|

An invertebrate model to evaluate virulence in Aspergillus fumigatus: The role of azole resistance

Abstract: The impact of different mutations in the Aspergillus fumigatus ergosterol biosynthesis pathway on pathogenesis has been evaluated using a simple invertebrate mini host, the caterpillar Galleria mellonella. A set of strains that includes clinical isolates and isogenic mutants with mutations at the cyp51A gene conferring azole resistance were studied. All strains demonstrated a similar in vitro growth pattern and are equally virulent against the insect larvae. These results suggest that in A. fumigatus acquisiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…In addition, the percentage and kinetics of conidial germination in Sab medium were similar for the mutants and the parental strain. These results confirmed that the mutations conferring resistance to azoles did not adversely impact fungal growth (16).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…In addition, the percentage and kinetics of conidial germination in Sab medium were similar for the mutants and the parental strain. These results confirmed that the mutations conferring resistance to azoles did not adversely impact fungal growth (16).…”
supporting
confidence: 76%
“…Isogenic A. fumigatus strains carrying different Cyp51A mutations exhibited no differences in virulence in the alternative host Galleria mellonella. However, that study did not look at competitive growth of strains within the host, preventing a proper evaluation of the fitness cost (16).…”
mentioning
confidence: 99%
“…25 In addition, the G. mellonella model appears to be a promising approach to evaluate fitness of drug-resistant strains. 43 Since VRC is the first line antifungal used to treat aspergillosis, we also analyzed the in vivo response of G. mellonella infected with A. fumigatus or A. lentulus and treated with this antifungal. G. mellonella was a useful model in the evaluation of the efficacy of VRC at concentrations equivalent to the therapeutic doses used in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The work of Slater et al (Slater et al 2011), demonstrating good correlation of virulence potential of wild type and mutant strains to murine models, highlights the eligibility of the larval model to be used with A. fumigatus. Therefore, numerous studies used Galleria to evaluate the contribution of gene deletion to virulence (Jackson et al 2009;Beckmann et al 2013;Gomez-Lopez et al 2014). A study by Cheema et al demonstrated that virulence of A. fumigatus differed depending on the mating type.…”
Section: Aspergillus Flavus Exhibits Highest Virulence Potential Of Amentioning
confidence: 99%